Perencanaan Dan Implementasi Kurikulum Merdeka di Madrasah Aliyah 2 Muhammadiyah Al-Furqan Banjarmasin - Asbi Kurniawati; Faiza Zahidah; Habibah Salwa; Fatwiah Noor (Journal Of Foreign Language Learning and Teaching, 2025)
This study aims to describe the planning and implementation of the Merdeka Curriculum at a private Madrasah Aliyah, with a focus on Arabic language instruction. A qualitative descriptive approach was employed through observation and documentation techniques. The findings show that the implementation of the Merdeka Curriculum is conducted gradually in line with the policy of the Ministry of Religious Affairs. Grades X and XI have adopted the Merdeka Curriculum, while grade XII continues to use the 2013 Curriculum. During the transition period, the school independently organized five teacher training sessions to support curriculum implementation. Due to the absence of an internal subject-based teacher forum (MGMP), the Arabic language teacher prepares teaching modules independently. One of the main challenges faced is the difficulty in mapping students’ initial competencies because diagnostic assessments have not been optimally implemented. In addition, students’ diverse educational backgrounds influence the effectiveness of Arabic language learning. To address these challenges, the teacher applies differentiated learning strategies by grouping students according to their achievement levels and implementing collaborative learning approaches. Efforts to enhance students’ interest and motivation in learning Arabic are also carried out through religious-based approaches that emphasize the integration of spiritual values in the learning process. The study concludes that institutional readiness, teacher initiative, and adaptive instructional strategies play a crucial role in supporting the successful implementation of the Merdeka Curriculum in private madrasah settings. Keywords : Implementation, Merdeka Curriculum, Planning